2015
DOI: 10.1158/2326-6066.cir-14-0163
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Targeting ROR1 in Primates with Chimeric Antigen Receptor–Modified T Cells

Abstract: Genetic engineering of T cells for adoptive transfer by introducing a tumor-targeting chimeric antigen receptor (CAR) is a new approach to cancer immunotherapy. A challenge for the field is to define cell surface molecules that are both preferentially expressed on tumor cells and can be safely targeted with T cells. The orphan tyrosine kinase receptor ROR1 is a candidate target for T-cell therapy with CAR-modified T cells (CAR-T cells) since it is expressed on the surface of many lymphatic and epithelial malig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 51 publications
5
116
0
1
Order By: Relevance
“…For future clinical trials, there is a pre-clinical development pipeline with CARs specific for target antigens in other hematologic and solid tumors, including a SLAMF7-specific CAR in multiple myeloma, and a ROR1specific CAR in lymphoma, breast and lung cancer (Berger et al, 2015;Hudecek et al, 2013). Importantly, the MC-encoded SB transposon can accommodate additional genetic cargo without compromising transposition efficacy.…”
Section: Clinical Trial With Car T Cells Engineered By Sleeping Beautmentioning
confidence: 99%
“…For future clinical trials, there is a pre-clinical development pipeline with CARs specific for target antigens in other hematologic and solid tumors, including a SLAMF7-specific CAR in multiple myeloma, and a ROR1specific CAR in lymphoma, breast and lung cancer (Berger et al, 2015;Hudecek et al, 2013). Importantly, the MC-encoded SB transposon can accommodate additional genetic cargo without compromising transposition efficacy.…”
Section: Clinical Trial With Car T Cells Engineered By Sleeping Beautmentioning
confidence: 99%
“…For example, clinical trials using viral-based gene transfer will test CARs specific for target antigens in other hematologic and solid tumors, including a SLAMF7-specific CAR for multiple myeloma and a ROR1-specific CAR for lymphoma, breast, and lung cancer [117,118]. The gene transfer technology enabled by SB to redirect T cell specificity can be extended beyond CAR.…”
Section: Transfectionmentioning
confidence: 99%
“…Zah et al [59] recently reported on the development of a bispecific CD19/CD20 CAR construct with increased anti-tumor effect and prevention of CD19-negative ALL outgrowth. CAR constructs against alternative targets like CD22 [60] or ROR1 [61] are currently in development.…”
Section: Discussionmentioning
confidence: 99%